The influence of parents on children’s consciousness of gender equality: a multi-group structural equation modeling approach - Li, Yifei; Zhang, Jie; Li, Juan; Chen, Yiping; Zhang, Jingping; Zuo, Man (Frontiers in Psychology, 2024)
Objective: This study aimed to understand the consciousness of gender equality among school-aged children in China and its influencing factors using structural equation modelling to explore the pathways, intensity and group differences among these factors.A cross-sectional survey was conducted using stratified random whole-group sampling of primary school students in grades 1-6 and their parents who met the inclusion and exclusion criteria. In this study, 1312 valid questionnaires were collected from a total of 1500 school-aged children in Hunan Province, China (effective response rate of 87.5%). Statistical analysis was conducted using SPSS 26.0 and AMOS 24.0 software. Statistical inference consisted of t-tests, analysis of variance, the LSD test, Pearson correlation analysis, multiple stepwise linear regression analysis and structural equation modelling.Results: School-aged children had the lowest consciousness of gender equality in the area of occupation and relatively higher consciousness in the areas of family and school. Children's age, gender, gender role, parent-child relationship, teacher-student relationship and parents' gender equality consciousness had predictive effects on children's consciousness of gender equality. The structural equation model constructed in this study is applicable to school-aged children of different genders. There was a significant difference in the structural equation modeling for children in different study period groups.In the education process, parents and teachers should attempt to improve their own consciousness of gender equality, integrate the concept of androgynous education, enhance close relationships with children, and adopt appropriate education methods according to the characteristics of different groups of children.